Design Of Noise Level Control To Reduce The Dosage Of Noise Exposure In Jakarta Electronic Companies - Mutiara N Sembiring (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
Noise is one of the physical hazard factors that are often encountered in the work environment. Continuous noise can cause discomfort at work. Jakarta Electronics Company is a company that produces electronic goods such as fans. The guard shop production unit is a production area that produces front guard and rear guard (fan product safety net). In the production unit there is a noise problem. Noise occurs at the level of 86 to 92 dB(A) and lasts for 7.8 hours/day, so it has exceeded the noise threshold value permitted by the government based on the Decree of the Minister of Manpower No. KEP.51/MEN/1999. This noise has the effect of hearing loss, feeling disturbed, fatigue, and impaired work communication.The research design used is a descriptive design using a survey method. Research variables include air temperature, noise level, duration of work, exposure to noise. Noise level and room temperature were measured using a 4 in 1 Multi Function Environment Meter. Other data is obtained from company record files.The measurement results show that the noise in the guard shop production unit has passed the threshold value with a noise range of 86 dB to 92 dB, which is in the area of ​​Middle Ring Welding, Cutting, Outer Ring Welding, Forming, , and Projection Welding machines.The design of the noise level management in the guard shop production unit is carried out by engineering control through the installation of barriers. The installation of the barrier will not interfere with the smooth flow of production at the guard shop production unit and other work stations